Feminised concern or feminist care? Reclaiming gender normativities in zero waste living. Issue 3 (May 2022) - Wilde, Mandy de; Parry, Sarah
Growing awareness of environmental issues and their relation to consumption patterns has given rise to calls for sustainable consumption across the globe. In this article, we focus on the zero waste lifestyle movement, which targets high-consumption households in the Global North as a site of change for phasing out waste in global supply chains. Our article is concerned with asking how gender and household sustainability are mutually constituted in the zero waste lifestyle movement. We establish an analytical tension between understanding zero waste living as a further intensification of feminised responsibility for people and the planet and as offering potential for transformational change – as feminised concern or feminist care. Through qualitative content analysis of the 10 most influential zero waste blogs globally, we show how the five zero waste rules of conduct – refuse, reduce, reuse, recycle, and rot – guide consumers towards everyday and situated engagements with waste. Organised by three cross-cutting themes – communing with nature, organising time, and spending money – we present the normativities these rules call into being for reconfiguring domestic activities such as cooking, cleaning, and grocery shopping. In the discussion, we draw out the implications of zero waste living's emerging, contradictory gender normativities, while recalling the political economy in which it is situated, namely a neoliberal, postfeminist landscape. We identify a continued feminisation of domestic responsibilities that is uncontested in zero waste living but also explore the progressive potential of waste-free living to bring collective, naturecultural worlds into being as part of domestic environmental labour.